Effect of intrauterine copper device on cervical cytology and its comparison with other contraceptive methods - Bagchi, Sipra; Sah, Shanti; Agrawal, Tanu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The intrauterine device (IUD) is the most commonly used reversible family planning method all over the world .The risk of cervical neoplasia associated with use of an intrauterine device (IUD), specially the copper releasing one, has been an important concern. The aim and objectives of the study was to determine safety of copper IUCD with regard to changes in cervical cytology and to compare the changes with other methods of temporary contraception. Methods: This was a prospective study carried out at a tertiary care institute for a period of 3 years. A total of 200 women of age group 18-40 years were included. 100 subjects who opted Cu-T 380A IUD were compared with 100 controls that had either opted other mode of temporary contraception like barrier, injectable, oral or did not use any method. Detailed history and examination of all subjects were done. All the women were subjected to conventional Pap smear and were followed at 6 months of interval for 1 year and then yearly up to 3 years. In each visit thorough pelvic examination was done and PAP smears were taken. Results: Among women using IUCD, 67.7% showed normal cytology as compared to 72.0% of the controls. On follow up, the incidence of normal cytology decreased (40%) with increased duration of use (up to 3 years). Incidence of inflammatory smear though first decreased up to 1 year (21.8%) but then gradually increased up to 2 years (37.0%) of use and then again decreased to 20.0% up to 3 years of use. ASCUS was found in only one case that used the device up to 2 years of use. LSIL was detected in 2 cases (20%) using IUD up to 3 years. No case of high grade intraepithelial lesion (HSIL) or invasive cancer was seen. Conclusions: There was no significant risk of cervical dysplasia or invasive carcinoma in IUCD users up to 2 years of use while other contraceptives (except barrier one) showed increased incidence of mild dysplasia (LSIL) after 1 year of use. Though risk of cervical malignancy is less with intrauterine copper devices, regular follow up should be done in long term users.